POPULATION DENSITY AND DISTRIBUTION PATTERNS OF KALAMBODO MUSSEL (Anodonta woodiana) IN THE SUB WATERSHED OF LAHOMBUTI RIVER, LAHOTUTU VILLAGE, KONAWE DISTRICT SOUTH EAST SULAWESI - Muhammad Fajar Purnama; Abdullah Abdullah; Alfi Kusuma Admaja; La Ode Alirman Afu (Jurusan Perikanan dan Kelautan, 2019)
Abstrak The research was conducted in November 2018 - February 2019 in the Sub-watershed of the Lahombuti River in Lahotutu Village, Konawe Regency. The purpose of this study was to determine aspects of population density and distribution patterns of the Kalambodo (A. woodiana) in the Sub watershed of the Lahombuti tributary in Lahotutu Village, Wonggeduku District, Konawe Regency. The sampling location was determined using the purposive random sampling method. Sampling of Kalambodo (A. woodiana) was carried out at the location with the greatest abundance of A. woodiana, in the Sub watershed of the Lahombuti tributary of Lahotutu Village, on the